I am here with you: an examination of factors relating to social presence in social VR - Son, Gayoung; Tiemann, Aline; Rubo, Marius (Frontiers in Virtual Reality, 2025)
Social VR is growing in popularity, with more users engaging in interactive VR platforms. A key aspect of these experiences is social presence, the feeling of being with others, which is essential in fostering meaningful connections and improving user engagement. While spatial presence and body ownership are considered important for social presence, interpersonal factors such as another person’s warmth or competence play an important role as well. In this study (N = 128), we examined the relationships between these four perceptions (spatial presence, body ownership, a partner’s warmth and competence) and social presence in social VR, both individually and while accounting for their combined effects. Multivariate analyses showed that spatial presence and partner warmth were robustly associated with social presence, whereas body ownership and competence were not significantly related to social presence. These patterns were consistent across interactions using anonymous avatars and non–anonymous avatars. We conclude that interpersonal perceptions, particularly warmth, should be considered alongside user experience variables when studying social presence. Furthermore, anonymized interactions in social VR likely preserve the underlying processes that support social presence.